A record of the last 460 thousand years of upper ocean stratification from the central Walvis Ridge, South Atlantic. (2nd August 2013) - Scussolini, Paolo; Peeters, Frank J. C.
<x xml:space="preserve">Abstract</x> [1] The upper branch of the Atlantic Meridional Overturning Circulation predominantly enters the Atlantic Ocean through the southeast, where the subtropical gyre is exposed to the influence of the Agulhas leakage (AL). To understand how the transfer of Indian Ocean waters via the AL affected the upper water column of this region, we have generated new proxy records of planktic foraminifera from a core on the central Walvis Ridge, on the eastern flank of the South Atlantic Gyre (SAG). We analyzed the isotopic composition of subsurface dweller Globigerinoides ruber sensu lato, and thermocline Globorotalia truncatulinoides sinistral, spanning the last five Pleistocene glacial‐interglacial (G‐IG) cycles. The former displays a response to obliquity, suggesting connection with high latitude forcing, and a warming tendency during each glacial termination, in response to the interhemispheric seesaw. The δ18O difference between the two species, interpreted as a proxy for upper ocean stratification, reveals a remarkably regular sawtooth pattern, bound to G‐IG cyclicity. It rises from interglacials until glacial terminations, with fast subsequent decrease, appearing to promptly respond to deglacial peaks of AL. Stratification, however, bears a different structure during the last cycle, being minimal at Last Glacial Maximum, and peaking at Termination I. We suggest this to be the result of the intensified glacial wind field over the SAG and/or of the invasion of the South Atlantic thermocline by Glacial North Atlantic Intermediate Waters. The δ13C time series of the two species have similar G‐IG pattern, whereas their difference is higher during interglacials. We propose that this may be the result of the alternation of intermediate water masses in different circulation modes, and of a regionally more efficient biological pump at times of high pCO2.